2019
DOI: 10.1177/1468795x19860111
|View full text |Cite
|
Sign up to set email alerts
|

The performance of citizen’s and organisational authority

Abstract: This article explores the interaction of two forms of authority: organisational authority and citizen’s authority. The concept of citizen’s authority derives from Pettit, and organisational authority has theoretical roots in Weber. Citizen’s authority entails the right to be the author of your own life decisions, while organisational authority is the right of an actor to speak on behalf of an organisation. With inspiration from Goffman and Austin, we take a performative ethnographic approach to the analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
8
0
4
Order By: Relevance
“…Dialog (dialogue) is the key governance concept that gives these actors their "reason to be" in Swedish governance. Calling them "experts" draws attention to the central dilemma of being a professional in a practice that is grounded in the critique of professional expertise (see Allmendinger, 2009;Mik-Meyer & Haugaard, 2019;Moore, 2017). Currently, the meaning of dialogue practice in Sweden is far from stabilised and settled.…”
Section: Dialogue Experts Power and Justificationmentioning
confidence: 99%
“…Dialog (dialogue) is the key governance concept that gives these actors their "reason to be" in Swedish governance. Calling them "experts" draws attention to the central dilemma of being a professional in a practice that is grounded in the critique of professional expertise (see Allmendinger, 2009;Mik-Meyer & Haugaard, 2019;Moore, 2017). Currently, the meaning of dialogue practice in Sweden is far from stabilised and settled.…”
Section: Dialogue Experts Power and Justificationmentioning
confidence: 99%
“…While it might seem contradictory, in the first case, sensitive observational work in video-recorded placement meetings led to an understanding of how homeless clients were perceived, unexpectedly, by service providers as both helpless individuals and active agents with authority. This spurred the team to be sensitive to the power held by the clients, not just to their helplessness in the circumstances (Mik-Meyer and Haugaard, 2020;Mik-Meyer and Silverman, 2019). In the second case, after visiting two research sites where employees with cerebral palsy worked, I discovered that the physical disability of the employees had profound effects on their relationships with their ablebodied colleagues.…”
Section: Nanna Mik-meyermentioning
confidence: 99%
“…So, othering is not a concept with just one meaning and a clear definition, as what it means to be 'othered' comprises different processes in different research fields and at different locations. In the field of disability, othering is closely linked to discourses of tolerance, equality and sameness (Mik-Meyer, 2017), whereas in the field of homelessness, othering is part of a discourse of agency and authority (Mik-Meyer and Haugaard, 2020;Mik-Meyer and Silverman, 2019). However, processes of othering encompass similarities across very different research fields as well.…”
Section: From Sensitizing Concepts To Empirical Complexitymentioning
confidence: 99%
“…We demonstrate that their actions are partly facilitated by a future‐oriented strategic interaction of placement meetings (e.g., where should the client live and which job should they have) and by their immediate interactions with their coparticipants. Mik‐Meyer and Silverman (2019) and Mik‐Meyer and Haugaard (2020) found that the organizational horizon also includes an emphasis upon client‐centeredness in placement meetings. Client‐centeredness is a norm emphasizing equal moral worth (we are all citizens) and that vulnerable clients' voice should be heard.…”
Section: Performing Agencymentioning
confidence: 99%